Pollen flora of Kastamonu university campus i: brassicaceae - Eltajouri, Mohamed Nuri; Ceter, Talip; Bani, Barış (Ankara University, 2018)
Plants used in this study were collected from Kastamonu University campus and its surrounding in Turkey. Samples prepared according to Wodehouse (1935) technique, and they were examined by light microscopy to study the characteristic of pollen grains. Pollen grains of studied taxa observed as isopolar, radially symmetric with tricolpate aperture and prolate-spheroidal, subprolate and prolate pollen shape. Polar axis range between 15.30-43.53 µm while equatorial axis between 13.48-29.09 µm. Alyssum strigosum pollen measured as biggest pollen while Strigosella africana pollen is the smallest. Pollen surface ornamentation determined as reticulate. Exine thickness and intine thickness were varied between 0.4-2.3 µm, 0.1-0.9 µm, respectively. The characters like as polar axis, equatorial axis, pollen shape, pollen surface ornamentation, intine and exine thickness determined as important features for systematics of taxa
Keywords: Brassicaceae; pollen; light microscopy (LM); Kastamonu University campus; Turkey